The effect of overnight sleep deprivation after competitive rugby league matches on postmatch Physiological and Perceptual Recovery - Skein, M.; Duffield, R.; Minett, G. M.; Snape, A.; Murphy, A. P. (International Journal of Sports Physiology and Performance, 2013)
Purpose: This study examined the effects of overnight sleep deprivation on recovery after competitive rugby league matches. Methods: Eleven male amateur rugby league players played 2 competitive matches, followed by either a normal night`s sleep (~8 h; CONT) or a sleep-deprived night (~0 h; SDEP) in a randomized fashion. Testing was conducted the morning of the match, immediately postmatch, 2 h postmatch, and the next morning (16 h postmatch). Measures included countermovement-jump (CMJ) distance, knee-extensor maximal voluntary contraction (MVC) and voluntary activation (VA), venous-blood creatine kinase (CK) and C-reactive protein (CRP), perceived muscle soreness, and a word-color recognition cognitive-function test. Percent change between postmatch and 16-h postmatch was reported to determine the effect of the intervention the next morning. Results: Large effects indicated a greater postmatch to 16-h-postmatch percentage decline in CMJ distance after SDEP than in CONT (P = .10-.16, d = 0.95-1.05). Similarly, the percentage decline in incongruent word-color reaction times was increased in SDEP trials (P = .007, d = 1.75). Measures of MVC did not differ between conditions (P = .40-.75, d = 0.13-0.33), although trends for larger percentage decline in VA were detected in SDEP (P = .19, d = 0.84). Furthermore, large effects indicated higher CK and CRP responses 16 h postmatch in SDEP than in CONT (P = .11-.87, d = 0.80-0.88). Conclusions: Sleep deprivation negatively affected recovery after a rugby league match, specifically impairing CMJ distance and cognitive function. Practitioners should promote adequate postmatch sleep patterns or adjust training demands the next day to accommodate the altered physical and cognitive state after sleep deprivation.